Development, Implementation and Evaluation of a Physical Activity and Nutrition Program for Older Adults Residing in Retirement Villages - Holt, Anne-Marie (Curtin University, 2017)
Physical activity and a healthy diet are recognised as important lifestyle factors for maintaining a healthy bodyweight and preventing chronic disease. Retirement villages are a unique setting to reach older adults to test the effectiveness of approaches to increase physical activity levels. improve nutrition and maintain a healthy bodyweight. This cluster-RCT based in Perth, Western Australia evaluated the effectiveness of a 6-month physical activity and nutrition program for ‘insufficiently’ active adults aged 60-80 years.